The Effectiveness of Ruxolitinib for Acute/Chronic Graft-versus-Host Disease in Children: A Retrospective Study - Yang W; Zhu G; Qin M; Li Z; Wang B; Yang J; Wang T (Dove Medical Press, 2021)
Wenli Yang,1,* Guanghua Zhu,2,* Maoquan Qin,2 Zhigang Li,3 Bin Wang,2 Jun Yang,2 Tianyou Wang2 1Department of Clinical Nutrition, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing, People’s Republic of China; 2Department of Hematology and Oncology, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing Key Laboratory of Pediatric Hematology Oncology, Key Laboratory of Major Diseases in Children, Ministry of Education, National Key Discipline of Pediatrics, Beijing, People’s Republic of China; 3Hematology and Oncology Laboratory, Beijing Pediatric Research Institute, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing Key Laboratory of Pediatric Hematology Oncology, Key Laboratory of Major Diseases in Children, Ministry of Education, National Key Discipline of Pediatrics, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tianyou WangDepartment of Hematology and Oncology, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing Key Laboratory of Pediatric Hematology Oncology, Key Laboratory of Major Diseases in Children, Ministry of Education, National Key Discipline of Pediatrics, Nanlishi Road No. 56, Xicheng District, Beijing 100045, People’s Republic of ChinaTel +86 10 5961 7123Fax +86 10 5971 8700Email wangtiany_wty@163.comObjective: This study aimed to evaluate the effectiveness of Ruxolitinib for acute/chronic graft-versus-host disease in children.Methods: This study was a retrospective trial. We analyzed the clinical characteristics of children who responded poorly to previous treatment for graft-versus-host disease (GVHD) and received ruxolitinib treatment after allogeneic hematopoietic stem cell transplantation (allo-HSCT) as an additional or replacement therapy.Results: A total of 53 patients were analyzed: aGVHD and cGVHD. The overall response rate (ORR) to ruxolitinib was 75.5%. The ORR was 64.7% (11/17) in the aGVHD group including 6, 5, and 6 patients with partial responses (PRs), complete responses (CRs), and treatment failure, respectively. The ORR was 80.6% (29/36) in the cGVHD group including 10 with CRs and 19 with PRs. Five and 2 patients showed no response and treatment failure, respectively. Four and 14 patients were GVHD recurrence in aGVHD and cGVHD respectively. A total of 14 patients (39%) discontinued steroids and 8 patients (22.2%) reduced steroids. The incidence of obvious adverse events was 94.1% (16/17) in the aGVHD group, which was higher than that in the cGVHD group. Meanwhile, the prognosis of children with cGVHD was superior to that of children with aGVHD after treatment with ruxolitinib. During the ruxolitinib treatment, only 1 patient suffered a relapse of the primary tumor. Eleven patients also suffered transplantation-associated thrombotic microangiopathy (TA-TMA) after allo-HSCT.Conclusion: Pediatric patients with GVHD (especially cGVHD) responded well to ruxolitinib treatment. Ruxolitinib can also be used as an alternative treatment for patients with TMA.Keywords: ruxolitinib, graft-versus-host disease, allogeneic hematopoietic stem cell transplantation, Janus kinase1/2 inhibitor, pediatric patients